An ecotoxicological assessment of the acute toxicity of anatoxin congeners on New Zealand Deleatidium species (mayflies). Issue 1 (2nd January 2020) - Kelly, Laura T.; Puddick, Jonathan; Ryan, Ken G.; Champeau, Olivier; Wood, Susanna A.
ABSTRACT: Toxic benthic cyanobacterial proliferations may pose a significant risk in freshwater ecosystems. In New Zealand, the only anatoxin-producing benthic species reported to date is Microcoleus autumnalis . Management of M. autumnalis proliferations has primarily focussed on mitigating the health risks associated with human and canine contact with the cyanobacteria. A major concern at the ecological level is the potential for lethal and sublethal effects on macroinvertebrates that may feed on toxic mats or use them as a refuge. In the present study, Deleatidium spp. (mayfly) larvae were exposed to different variants of purified anatoxins (anatoxin-a, dihydroanatoxin-a, and a mixture of homoanatoxin-a/dihydrohomoanatoxin-a). No significant mortality of Deleatidium spp. larvae occurred, even at doses far exceeding likely environmental exposures (300–600 μg L −1 ). Deleatidium spp. larvae exposed to high doses of dihydroanatoxin-a had measurable concentrations of the toxin in their tissues 24 h post-exposure. The results of this study indicate that anatoxins from benthic M. autumnalis proliferations are unlikely to result in mortality of Deleatidium spp. larvae, although the effect on all stages of the lifecycle and on crude extracts from M. autumnalis is unknown. Uptake of anatoxins in the tissues of macroinvertebrates may represent a pathway for anatoxin transfer up trophic levels, and further study is required.